Reproducibility of tissue autofluorescence for screening potentially malignant disorders - Fricain Jean-Christophe; Fenelon Mathilde; Baschet Louise; Catros Sylvain; Glock Nicolas; Lerici Sébastien; Gaston Rémi; Perez Paul; Doussau Adélaide (EDP Sciences, 2020)
Introduction: Direct tissue autofluorescence (AF) visualization devices such as VELscope® are gaining interest to improve early detection of oral potentially malignant disorders (OPMD) and cancers. The main objective of this study was to assess inter-observer reproducibility of incandescent light (IL) and AF observations for OPMD and cancer. Materials and methods: High risk patients (exposed to alcohol or tobacco) were screened by two independent operators with a conventional oral examination (IL) followed by AF examination. The primary endpoint was the inter-observer agreement on the decision to biopsy assessed by kappa coefficients.Accuracy of IL and AF were estimated by the relative true positive rate (RTPR, increase of sensitivity), relative false positive rate (RFPR, loss of specificity) and their ratio. Results: 179 patients were included. 833 lesions were identified after IL and AF. Indication for biopsy was retrieved for 41 patients (61 lesions). Inter-observer agreement on the indications for biopsy was 93.3% after IL (Kappa coefficient 0.88 [0.80, 0.97]) and 96.1% after IL and AF (Kappa coefficient 0.78 [0.66, 0.90]). RTPR was 1.2, RFPR was 1 and their ratio was 1.2. Conclusion: IL and AF examination has shown good inter-observer reproducibility. Adjunction of AF allowed diagnosing more leukoplakia without dysplasia.